THE THEORETICAL APPROACHES, PEDAGOGICAL TERMS AND PRACTICAL WAYS OF PREVENTING MYOPIA IN PRIMARY SCHOOLERS (Education in the 21st Century, 2023)
This article presents the theoretical approaches, pedagogical terms and practical ways to theorganization and prevention of myopia in primary schoolers. It is commonly known, that myopiais often observed at school age, when a child does not follow the rules, regulations, andrequirements set for the protection of vision and visual work during games, drawing, viewingpictures and drawings, computer activities, etc. This determines the necessity of versatile and deepstudying of this issue and developing of theoretical approaches, pedagogical terms and practicalways for prevention of myopia in primary schoolers.The literary data and work experience indicate that the role of the school is immeasurablyincreasing in the general system of a child development, in strengthening the health of pupils,shaping the personality and preventing myopia. Unfortunately, may teachers do not pay neededattention to the conditions of conducting the child’s visual work, and often do not have thenecessary information about the rules and standards of visual work and rest of the child’s eyes.Therefore, the study of many aspects of this problem and the development of theoreticalapproaches, pedagogical terms and practical ways for the organization and prevention of myopiain primary schoolers will be the basis for a successful solution of this problem and maintaininggood vision in children.